2006
DOI: 10.1089/jwh.2006.15.281
|View full text |Cite
|
Sign up to set email alerts
|

Microbicide Preference among Young Women in California

Abstract: Our findings help illustrate microbicide product preferences and demand among young women in California, and the methodological approach should lend itself to other populations as well as during clinical trials when understanding product use and nonuse is critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 24 publications
3
48
1
5
Order By: Relevance
“…However this observation, This study suggests that professionals would support which challenges the widely acknowledged power female-controlled HIV/STI prevention options particularly imbalance with respect to sexual decisions in favor of the the vaginal microbicides, a finding which is similar to earlier 23 12,13, [22][23][24] men, should be interpreted with caution. It is likely that this reports from other parts of the world.…”
Section: Discussionsupporting
confidence: 61%
“…However this observation, This study suggests that professionals would support which challenges the widely acknowledged power female-controlled HIV/STI prevention options particularly imbalance with respect to sexual decisions in favor of the the vaginal microbicides, a finding which is similar to earlier 23 12,13, [22][23][24] men, should be interpreted with caution. It is likely that this reports from other parts of the world.…”
Section: Discussionsupporting
confidence: 61%
“…Also, as in other studies, we found that younger women were more likely to report that side effects would affect their likelihood of using the product. 11,15 Previous research suggests that women may not attempt, may reduce the amount, or may discontinue product use if the microbicide causes irritation, excessive leakage, or wetness. 6 The results also suggest that women who had a greater lifetime number of sex partners were more interested in protection features, although this finding was marginally significant.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] These studies suggest that several factors may influence microbicide acceptability, including a woman's sociodemographic characteristics, personal risk (real or perceived), cultural norms and practices, side effects, and the smell or taste of a product. [3][4][5][6][7][8][9][10][11][12][13][14][15] An increased understanding of which attributes of a microbicide are most appealing to women at increased risk for STDs may help ensure that effective products are used.…”
mentioning
confidence: 99%
“…Studies investigating microbicide development and use typically utilize convenience samples recruited via word of mouth, flyers, and outreach, often at a variety of community-based organizations (Coggins et al, 1998;Hammett, et al, 2000a, b;Holt et al, 2006;Mason et al, 2003). Weeks et al (2004) used targeted sampling with outreach and referrals to recruit a sample of women at high risk for HIV infection.…”
Section: Introductionmentioning
confidence: 99%